A method for TCP congestion control in multi-hop wireless network - Othman, Mohamed; Al-Jubari, Ammar (2014)
The present invention relates to a method for managing congestion in a wireless network. It deploys the step of observing RTT and IAT of TCP ACK value to estimate the current network conditions (200); conducting increase-decrease of cwnd of the rate of TCP (300); and conducting loss reaction mechanism whenever TCP detects the loss by duplicate ACK or timeout (400). The present invention efficiently estimates the network condition, distinguishes between losses, and adaptively controls the data packet transmission is required.